Implementasi Model Project Based Learning dalam Penanaman Karakter Sesuai Nilai-Nilai Pancasila Kelas 5 SDN Bandung 1 - Wulandari, Rista Febi; Rochmania, Desty Dwi (Jurnal Simki Postgraduate, 2025)
This study aims to implement Pancasila using the Project Based Learning model, the reason researchers use this model is that class teachers more often use learning resources in the form of textbooks and sometimes make their own worksheets that are less interesting for students, this results in students looking less enthusiastic and learning becomes less meaningful. Through this learning model, students "are expected to be more involved and enthusiastic in learning through Pancasila education, which will have an impact on the development of their character, intellectual capacity, and personal growth in accordance with the principles of Pancasila outlined in the independent learning course. This research method uses a qualitative method with descriptive analysis techniques, data collection techniques using the triangulation method, namely collecting information from various sources (eg interviews, observations, and documentation); while the research subjects were 21 students in grade 5 of SDN Bandung. The results of the study after being applied in grade 5 using the project based learning model can help students grow as individuals in line with the principles outlined in Pancasila". Based on observations and analysis of the results of the problems given to students, there is an increase in several aspects of character, namely being devoted to God Almighty (1st principle), respecting others (2nd principle), global diversity (3rd principle), deliberation (4th principle), being fair to fellow human beings (5th principle). Students involved in collaboration-based projects are more likely to demonstrate attitudes of cooperation and helping each other to achieve common goals.